Characterization of ADRB2-mediated antitumoral effects and mechanisms of action of β-blocker propranolol in osteosarcoma - Solernó, Luisina María (2022)
Osteosarcoma (OSA) is still associated with limited response to standard-of-care therapy and alarmingly elevated mortality rates. Our group recently reported for the first time that PPN, a repurposed β1/2-adrenergic receptor (ADRB1/2)antagonist, was capable of reducing tumor-associated angiogenesis and xenograft aggressiveness using different OSA preclinical models.The objective of this work was tocharacterize PPN ADRB2-mediated effects and mechanisms of action on OSA growth, migration and response to chemotherapy. After confirming ADRB2 expression by RT-qPCR in MG-63 and U-2OS OSA cells, pro-mitogenic effects of ADRB agonists epinephrine and norepinephrinewere associated with downstream activation of MAPK-associated signaling pathways, as evaluated by western blotting. ADRB2 knockdown by transfection with ADRB2-targeting siRNA reduced in vitro aggressiveness of OSA cells and impairedPPN cytostatic activity, confirming target specificity of the drug. As evaluated by flow cytometry, a significant arrest in the G0/G1 cell cycle phase of MG-63 and U-2OS cells was observed after 24 h treatment with PPN (50 µM), which was associated with a significant reduction in CCND1 gene expression, a key cell cycle regulator. OSA growth inhibition was not associated with apoptosis induction. β-blockade with PPN inhibited OSA cell chemotaxis, vasculogenicmimicry and capillary-like tube formationon Matrigel® coated substrates. Migration inhibition was linked toblockade of EGF-induced actin reorganization and stress fiber formation. After histological analysis, in vivo therapeutic benefits after addition of PPN (10 mg/kg i.p.) to cisplatin-based metronomic chemotherapy (2 mg/kg i.p.) correlated with reduced tumor mitotic index and increased necrosis. All results were significantat p<0.05 (t test or ANOVA, GraphPad Prism). We propose PPN as a potential cost-effectiveco-adjuvant therapy for OSA management. Further translational studies on metastatic disease are in progress.